Effects of Strategic Management Drivers on Performance of Airports in Kenya - Koros, Rosemary Chebet; Namusonge, Prof. G. S.; Sakwa, Prof. M.M. (IJRDO - Journal of Applied Management Science, 2017)
The main objective of this study is to establish the effect of strategic management drivers onperformance of airports in Kenya. This study is guided by the following specific objectives:- tofind out the effects of strategic human capital on performance of airports in Kenya, to establishthe effects of safety and security strategy on airports performance in Kenya, to determine theeffects of strategic customer focus management practices on airports performance in Kenya, andto establish the effects of use of strategic ICT on airports performance in Kenya . The study isbased on the Contingency theory and Stakeholder theory. The study will adopt correlationalresearch design and will use both statistics (quantitative) and themes (qualitative) to developstrong evidence in support of the study variables.The target population of the study comprises of 2078 respondents cutting across the whole organization ranging from senior managers to staffthat are directly linked to the airports operations from all the airports in Kenya.